A survey study on the assessment of food handler’s compliance to personal hygiene practices regulation in selected Malaysia food outlets​ - Elexson, N.; Buyong, N. L.; Lesen, D.; Basiron, M. M.; Ahad, N.; Wan Jesfrydi, W. N. Q.; Jamaludin, M. H.; Fadilah, M. F. A.; Azra, T.; Tunung, R. (Rynne Lyan Resources, 2023)
Food safety remains a major issue around the world particularly when the COVID-19 pandemic becomes the main issue nowadays. Food safety is essential to the human population worldwide because food is the primary energy source and nutrition for humans. Therefore, food handlers' personal hygiene is one of the factors that are necessary to maintain food safety. The purpose of this study was to assess the food handler’s compliance with personal hygiene practices in randomly any food outlets across Malaysia including Kuching, Sarawak; Lawas, Sarawak; Johor Bahru, Johor; Kuala Penyu, Sabah, and Gurun, Kedah. A quantitative method, a cross-sectional descriptive study to one thousand and five (N = 1005) food handlers who participated in the questionnaire and observation checklist was developed by modifying questions in accordance with the Food Hygiene Regulations 2009. Overall, the mean percentage of conformity in adhering to food handler attire was the highest observed at Gurun, Kedah and Kuala Penyu, Sabah with 86.96% and 80.79%, respectively, followed by Kuching, Sarawak with 77.5%, Johor Bahru with 76.71%, and Lawas, Sarawak with 74.93%. Personal hygiene practices conformity showed a high mean percentage with all districts scoring >91% higher than non-conformity. The food handlers also show less unhygienic behaviour while on duty and scored a mean percentage of > 92%. Although in that positive behaviour, some of the food handlers did not perform some unhygienic practices (≤ 8 %). In conclusion, there is no significant difference (p-value > 0.05) in the level of conformity between the mean percentages among all districts. Thus, this issue shall raise a concern to the food industries in order to make sure their workers comply with the legal requirement and to avoid any food poisoning outbreak related to food hygiene and food safety in the future.